(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
The article examines the interrelation between idiolect and conceptosphere in modernist literary texts. The study is based on the theoretical assumption that an author’s individual language is not only a stylistic marker but also a mechanism that activates conceptual meaning. Modernist prose is especially productive for this purpose because its semantic structure is often built through indirect expression, syntactic economy, repetition, silence and implicit meaning. The paper discusses the works of Ernest Hemingway, Virginia Woolf, William Faulkner, Gertrude Stein and F. Scott Fitzgerald as a general literary context, while Hemingway’s minimalist prose is treated as a particularly illustrative case. The analysis shows that concepts such as time, memory, fear, courage, life and death are often not directly explained in modernist texts; rather, they are reconstructed by the reader through recurrent idiolectal features. The article argues that the conceptosphere of a literary text cannot be adequately described without considering the individual language of the author. This approach is relevant for both literary interpretation and translation studies, since the loss of idiolectal markers may lead to the weakening of conceptual meaning in translation.